ANALISIS KEPUTUSAN PEMBELIAN MELALUI CITRA MEREK DAN PERSEPSI HARGA PADA PT. HUMPUSS TRADING JAKARTA - Yulianingsih, Yulianingsih; Kartini, Tini; Kurniawan, Dede (INOVATOR, 2020)
The research aims to analyze the relationship between brand image and price perception with purchasing decisions at PT. Humpuss Trading, Jakarta. The study population was 140 customers and the number of samples 104 respondents using proportional random sampling technique. The research method used was a survey with a correlational approach consisting of two independent variables namely brand image and price perception and one dependent variable, namely purchasing decisions. The results showed that there was a positive and significant relationship between brand image and purchase decision, there was a positive and significant relationship between price perception and purchase decision, there was a positive and significant relationship between brand image and price perception simultaneously with purchase decisions. Thus it can be concluded that purchasing decisions can be improved through brand image and price perception partially or simultaneously.